THE ROLE OF LARGE CITIES IN MODERN ARMED CONFLICTS Part 1 - Целуйко, В. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The phenomenon of combat transfer into large cities in modern armed conflicts is examined in this Article. The first part of the Article is devoted to their military component. The mixed classification of populated locations applied with elements of Post-Soviet and Anglo-Saxon military science is introduced. Military purposes for transfer of armed actions into a large cities as well as a wide spread forms of such actions are considered.